The Importance of Enduring and Consolidating Liberal Education in the Higher Learning Institution of Asian Countries - Shaffarullah Abdul Rahman; Romzi Ationg; Saidatul Nornis Mahali (2020)
The liberal education and specifically its core subjects that includes humanities, social sciences and fine arts are at the risk in Higher Learning Institution (HLI) of Asian countries due to forced reorientation of HLI to assume market needs. This paper argues, however, that enduring as well as consolidating the liberal education in HLI of Asia is vital for not only providing the students with knowledge essential to their future career but also to ensure the maintenance of Asian values. Nonetheless, to introduce this argument, it will be necessary to acknowledge how the liberal education can actually provide the students of HLI with knowledge essential to their future career and helps maintain Asian values. Accordingly, by analyzing various sources such as books, journals, newspapers, blogs, facebook and interview with few randomly selected respondents, this paper presents the importance of enduring and consolidating the liberal education in the HLI of Asian countries. This paper starts with a discussion on what exactly is the meaning of liberal education and ended with some suggestions on how the liberal education should be endured and consolidated in Asian countries as well as at the global level.